Diversidade e distribuição espacial de anfíbios anuros do Parque Estadual do Turvo, Rio Grande do Sul - Iop, Samanta (2010)
We study the richness and the spatial distribution of anuran amphibians recorded in Parque Estadual do Turvo (PET), the largest remnant of Mesophytic Semideciduous Forest in the state of Rio Grande do Sul, Brazil. In this study we (1) describe the composition of community of amphibians in PET, (2) compare the composition of species with those recorded in other localities of Seasonal Forests, testing the hypothesis that localities nearest the Misiones Nucleus support the current proposal of a new phytogeographic unit, known as Seasonal Rain Forest Region , and (3) we tested if the occurrence of breeding pond anurans differed from a null model of random placement, as well as we hypothesized that the environmental heterogeneity and spatial distribution of ponds influences the structure of anuran communities in southern Brazil. The species inventory was carried out using complementary sampling techniques (surveys at breeding sites, casual encounters, pitfall traps and search at scientific collections). To check the spatial distribution, we monitored 14 ponds with variable heterogeneity. We recorded 32 species of amphibians in the Park area, belonging to two orders: Anura, 30 native and one exotic species, and Gymnophiona, one species. The analysis of similarity among the localities of seasonal forests evidenced three groups with similarity of 45%: the former group was composed by localities of southeast and central-western Brazil, the second group was composed by southern localities, and the third group was composed by localities of the transition area with the Atlantic Forest sensu stricto. The second group supports the proposal of a new phytogeographic unit, known as 'Tropical Seasonal Forests Region'. We recorded 15 anuran species at the monitored ponds, and the species occurrence was clearly not random, corroborating our hypothesis that the anuran composition of species is influenced by environmental heterogeneity. The main descriptors of pond heterogeneity correlated with abundance of anuran species were area, depth, hydroperiod, percentage of vegetation cover on water surface, and distance of pond in relation to the nearest Park edges. The community structure of anurans was not affected by the geographical distribution of ponds. The results of the present study demonstrate that the heterogeneity of water bodies is a strong regulator of community structure of breeding pond amphibians and this information has implications for conservation strategies of Neotropical Austral anurans.